2022
DOI: 10.3390/ijerph19137916
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic and International Students’ Mental Health in China: Age, Gender, Chronic Health Condition and Having Infected Relative as Risk Factors

Abstract: International students in China were among the first group of individuals to be affected by the COVID-19 pandemic. However, the pandemic’s impact on their mental health is underexplored. This study—utilizing web-based survey data (N = 381), presents preliminary reports using ANOVA and MIMIC analytic approaches. Following the clinical demarcation of the 21-item version of the Depression Anxiety Stress Scales (DASS-21), we found 24.6%, 38.3%, and 43.6% of the students to suffer mild to extreme stress, anxiety, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 63 publications
0
9
0
1
Order By: Relevance
“…Flights were not resumed so they were not able to go back their countries, so these all factors impacted that quality of life and well-being. 46 The global research regarding the psychological effects on the populous of this pandemic and the lockdown has been limited in both number and quality, mostly due to targeted sampling, improper medical sampling techniques, and lack of pre-pandemic data to compare the results against. A study showed that mental stress has increased in the US since 2018, especially in young adults (18-24 years of age).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flights were not resumed so they were not able to go back their countries, so these all factors impacted that quality of life and well-being. 46 The global research regarding the psychological effects on the populous of this pandemic and the lockdown has been limited in both number and quality, mostly due to targeted sampling, improper medical sampling techniques, and lack of pre-pandemic data to compare the results against. A study showed that mental stress has increased in the US since 2018, especially in young adults (18-24 years of age).…”
Section: Introductionmentioning
confidence: 99%
“…Flights were not resumed so they were not able to go back their countries, so these all factors impacted that quality of life and well-being. 46 …”
Section: Introductionmentioning
confidence: 99%
“…Коллинз Антви c соавторами, исследуя иностранных студентов (N = 381) в китайских вузах [Antwi et al, 2022], обнаружили, что студенты, у которых есть родственники, зараженные вирусом (по сравнению с теми, у кого их не было), испытывали значительно более высокий уровень беспокойства и стресса. Те, кто сообщил о ранее существовавших хронических заболеваниях (по сравнению с теми, у кого их не было), также сообщили о значительно более высоком уровне стресса, тревоги и депрессии.…”
Section: уровень изученности проблемыunclassified
“…Several studies find some mental health deterioration in China among specific groups during the pandemic. These contributions focus on specific groups rather than on the whole population: COVID-19 patients ([8] [9] [10]); university and college students ([11] [12] [13] [14]); children and adolescents ([15] [16] [17] [18]); or other subgroups of the population ([19] [20] [21] [22] [23]). Furthermore, several of these China-based contributions use data collected during the pandemic through non-representative and mostly online surveys (e.g.…”
Section: Introductionmentioning
confidence: 99%